Effect of local sea cucumber (Phyllophorus sp.) methanol extract as natural antifouling against macrofouler (Nerita sp.) - Hasanah, Himatul; Maisaroh, Dian Sari; Perdanawati, Rizqi Abdi (UIN Sunan Ampel Surabaya, 2021)
This study aims to find out the activities of local sea cucumber methanol extract (Phyllophorus sp.) as a natural antifouling against macrofouler Nerita sp. This study uses experimental methods laboratory. Laboratory-scale data collection is carried out by observation of biota paste activities fouling on the aquarium (antifouling rate) as well as its regaining rate. This research uses research design complete random design (RAL) with three repetitions. Local sea cucumber methanol extract (Phyllophorus sp.) contains bioactive compounds such as saponins, alkaloids, tannins, steroids and phenolics. Methanol Extract local sea cucumber (Phyllophorus sp.) affects the antifouling rate by reducing the Nerita sp. macrofouler paste rate with increasing concentration. It's the same thing,occurs where the increasing concentration of local sea cucumber methanol extract (Phyllophorus sp.) provides a significant decrease in Nerita sp. macrofouler regaining capability. The results lethal concentration 50 or LC50 obtained a value of 185.18. This means the concentration of the extract sea cucumber (Phyllophorus sp.) is deadly 50% of all biota test at a concentration of 185.18 mg/ml. Based on antifouling rate analysis and regaining rate it is known that the concentration of the most effective that can be used as an antifouling is a concentration of 75 mg/ml. This is because a concentration of 75 mg/ml of local sea cucumber methanol extract (Phyllophorus sp.) can already inhibit paste macrofouler Nerita sp. The concentration of 75 mg/ml also has a large regaining rate of 85%.